Differences in post‐traumatic stress, anxiety and depression following miscarriage or ectopic pregnancy between women and their partners: multicenter prospective cohort study. (2nd January 2021) - Farren, J.; Jalmbrant, M.; Falconieri, N.; Mitchell‐Jones, N.; Bobdiwala, S.; Al‐Memar, M.; Tapp, S.; Van Calster, B.; Wynants, L.; Timmerman, D.; Bourne, T.
ABSTRACT: Objectives: To investigate and compare post‐traumatic stress (PTS), depression and anxiety in women and their partners over a 9‐month period following miscarriage or ectopic pregnancy. Methods: This was a prospective cohort study. Consecutive women and their partners were approached in the early pregnancy units of three hospitals in central London. At 1, 3 and 9 months after early pregnancy loss, recruits were e‐mailed links to surveys containing the Hospital Anxiety and Depression Scale and the Post‐traumatic Stress Diagnostic Scale. The proportion of participants meeting the screening criteria for moderate or severe anxiety or depression and PTS was assessed. Mixed‐effects logistic regression was used to analyze differences between women and their partners and their evolution over time. Results: In total, 386 partners were approached after the woman in whom the early pregnancy loss had been diagnosed consented to participate, and 192 couples were recruited. All partners were male. Response rates were 60%, 48% and 39% for partners and 78%, 70% and 59% for women, at 1, 3 and 9 months, respectively. Of the partners, 7% met the criteria for PTS at 1 month, 8% at 3 months and 4% at 9 months, compared with 34%, 26% and 21% of women, respectively. Partners also experienced lower rates of moderate/severe anxiety (6% vs 30% at 1 month, 9% vs 25% at 3 months and 6% vs 22% at 9 months) and moderate/severe depression (2% vs 10% at 1 month, 5% vs 8% at 3 months and 1% vs 7% at 9 months). The odds ratios for psychological morbidity in partners vs women after 1 month were 0.02 (95% CI, 0.004–0.12) for PTS, 0.05 (95% CI, 0.01–0.19) for moderate/severe anxiety and 0.15 (95% CI, 0.02–0.96) for moderate/severe depression. Morbidity for each outcome decreased modestly over time, without strong evidence of a different evolution between women and their partners. Conclusions: Some partners report clinically relevant levels of PTS, anxiety and depression after pregnancy loss, though to a far lesser extent than women physically experiencing the loss. © 2020 International Society of Ultrasound in Obstetrics and Gynecology